Diabetes mellitus and the metabolic syndrome – the common problem - Cypryk, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2006)
In the article the author present current and compulsory diabetes mellitus diagnostic criteria. Some aspects of etiology and pathophysiology of diabetes mellitus type 2 have been also discussed; including insulin resistant and insulin secretion disturbances. The authors present goals of therapy and treatment methods according. The emphasis is put on good metabolic control which brings the best results regarding decrease in number of all chronic complications.